Spoils in the Roman Republic. Boon and bane, ed. Marian Helm, Saskia T. Roselaar, Stuttgart 2023, ss. 467 - Jarych, Adam (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2024)
Recenzja książki Spoils in the Roman Republic. Boon and bane, ed. Marian Helm, Saskia T. Roselaar, Stuttgart 2023, ss. 467